2020
DOI: 10.3390/polym12081643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Temperature Exposure on the Mechanical Properties of Kenaf Composites

Abstract: Automotive parts, including dashboards and trunk covers, are now fabricated through a compression-molding process in order to produce lightweight products and optimize fuel consumption. However, their mechanical strength is not compromised to avoid safety issues. Therefore, this study investigates kenaf-fiber-reinforced polypropylene composites using a simple combing approach to unidirectionally align kenaf fibers at 0°. The kenaf composite was found to withstand a maximal temperature of 120 °C. The tensile an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This selection was due to higher modulus and resistance achieved during tensile and flexural tests. The fique fibers oriented parallel to the applied load during the mechanical tests and the stiffening effect of the fibers allowed to obtain a rigid biocomposite material with tensile and flexural strength (36.6 and 21.2 MPa, respectively) comparable to other automotive commercial products reported in the literature 18 . Also, the resin film infusion processing could generate a considerable pressure within the mold, which then allows for a homogeneous compaction of fique fibers and EP during the curing.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…This selection was due to higher modulus and resistance achieved during tensile and flexural tests. The fique fibers oriented parallel to the applied load during the mechanical tests and the stiffening effect of the fibers allowed to obtain a rigid biocomposite material with tensile and flexural strength (36.6 and 21.2 MPa, respectively) comparable to other automotive commercial products reported in the literature 18 . Also, the resin film infusion processing could generate a considerable pressure within the mold, which then allows for a homogeneous compaction of fique fibers and EP during the curing.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies performed on PP-Kenaf 18 and HDPE-henequen 19 biocomposites suggested that biocomposites with fibers oriented parallel to the applied load (0°) were able to contribute the same applied load and possessed a much longer fiber structure due to minimal fiber breakage. Thus, aiding in the strengthening of the biocomposite structure due to a homogeneous distribution of the load.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The supports and the load, which are presented as a cylinder with a diameter of 5 mm, were modelled as rigid. The modulus was obtained from the experiment and density, and Poisson's ratios were 1.29 g/cm 3 and 0.37 [24,25], respectively. Coulomb friction was used to model the friction between surfaces with a coefficient equal to 0.2 [26].…”
Section: Resultsmentioning
confidence: 99%
“…The inherent biodegradability, renewability and non-toxicity potentials of kenaf fibres is attracting increasing attention. The utilisation of kenaf fibre as reinforcement agent in composite applications has been extensively reported in literature [ 3 , 4 , 5 ]. Ariawan et al [ 6 ] incorporated kenaf fibre for the reinforcement of composites and reported improved mechanical and thermal properties compared to unreinforced kenaf fibre.…”
Section: Introductionmentioning
confidence: 99%